Proposta curricular de Santa Catarina: um lugar de confronto entre o discurso pedagógico e o discurso científico - Prudêncio, Perpétua Guimarães (2004)
The present work, based on the theoretical and analytic devices of the Analysis of the Speech (PÊCHEUX, 1969 and 1975, and ORLANDI, 1983,1990,1999), analyzes the text of the Curricular Proposal of Santa Catarina and an exemplary text of Plan of Discipline in order to understand how texts which have as purpose to be complementary are confused. Because of it, it was confronted some senses built in the text of the Proposal with some senses built in a plan of exemplary discipline; so that, in this confrontation the estrangement was evidenced among the virtual readers, in other words, among the authors of the respective texts. The school as an institutional responsible space for those texts was also considered. Through its discursive practices which involve the production/connection/reproduction of the knowledge (scientific), it was possible to reflect on the operation of the pedagogic speech (PS), predominant in this conjuncture in its relation with the scientific speech (SS). That way, the analysis showed the imaginary that constitutes the reader for the authors of Curricular Proposal’s text is the reader who is a member of the scientific community. However, the common reader of that text with his/her material determinations (historical/social), is that teacher who is not part of the scientific community because when he/she is, he/she feels as a strange to the process of knowledge production and, therefore, he/she does not have a position as a member of the scientific community. As a result of this, the teacher, real reader of text of the Curricular Proposal, is unable to unchain the process of significance of the referred text